Detection of Thermal Emission at Millimeter Wavelengths from Low-Earth Orbit Satellites - Allen Foster; A. Chokshi; A. J. Anderson; B. Ansarinejad; M. Archipley; L. Balkenhol; K. Benabed; A. N. Bender; D. R. Barron; B. A. Benson; F. Bianchini; L. E. Bleem; et al. (The Open Journal of Astrophysics, 2025)
The detection of satellite thermal emission at millimeter wavelengths is presented using data from the 3rd-Generation receiver on the South Pole Telescope (SPT-3G). This represents the first reported detection of thermal emission from artificial satellites at millimeter wavelengths. Satellite thermal emission is shown to be detectable at high signal-to-noise on timescales as short as a few tens of milliseconds. An algorithm for downloading orbital information and tracking known satellites given observer constraints and time-ordered observatory pointing is described. Consequences for cosmological surveys and short-duration transient searches are discussed, revealing that the integrated thermal emission from all large satellites does not contribute significantly to the SPT-3G survey intensity map. Measured satellite positions are found to be discrepant from their two-line element (TLE) derived ephemerides up to several arcminutes which may present a difficulty in cross-checking or masking satellites from short-duration transient searches.